Model Deteksi Dini Anemia pada Ibu Hamil sebagai Solusi Inovatif Pencegahan Stunting bagi Petugas Kesehatan di Puskesmas Kota Palu - Sisilia Rammang; Agnes Erlita Distriani Patade (Jurnal Ners, 2025)
Anemia in pregnant women is a critical health issue in Palu City and represents a major risk factor for childhood stunting. This study aims to develop an early detection model for anemia in pregnant women as an innovative effort to prevent stunting for healthcare providers. Methods: This research employed a quantitative design with a cross-sectional approach involving 100 healthcare providers from three Community Health Centers (Puskesmas) in Palu City. Data were collected using questionnaires and analyzed with Structural Equation Modeling - Partial Least Squares (SEM-PLS). Results: The model was able to explain 50.7% of the variation in the Early Detection of Anemia variable (Y). The main findings indicate that Feedback and Role (M2) of healthcare providers had the strongest and most significant positive influence on Early Detection of Anemia (Y), with a path coefficient of 0.963 (p<0.05). Demographic factors (X1) and Workload (X2) were found to significantly influence the mediating variables, but did not directly and positively affect Y. The direct effect of Workload on Y was not significant, while Demographic factors had a negative effect on anemia detection (Y). Conclusion: The active role of healthcare providers is the most essential predictor of success in early detection of anemia, serving as a key mediator. Therefore, the most effective interventions should focus on strengthening and empowering the active role of healthcare providers as the frontline of care delivery.